Celebrity and entertainment obsession : understanding our addiction - Levy, Michael S., 1953- (Lanham, Maryland : Rowman & Littlefield, 2015)
Celebrity culture surrounds us. We are inundated with information about actors and actresses, athletes, musicians, and others who have become famous or infamous. Although we never will likely meet or get to know them, our interest in them seems boundless. We are literally obsessed with being entertained as well as with the people who entertain us. Who our celebrities are has also shifted; in the past, celebrity status was bestowed on men and women of great accomplishment, those who had given the world something to be proud of and to celebrate. Conversely, today's celebrities are generally people involved in entertainment--from TV newscasters to people who appear on reality television programs, as well as some who are simply famous for being famous. What remains an enigma is why we, as a society, are so infatuated with being entertained, as well as with those who entertain us and appear in the media. This book makes sense of this spectacle by explaining the reasons for this obsession from a psychological, social, and historical perspective. It suggests that we have become addicted in much the same way that a person becomes addicted to drugs or alcohol. Finally, the author offers his observations on how to free our minds from this captivation. Anyone interested in understanding more about our need to live vicariously through the rich and famous will find answers in this book.
Introduction -- The human species -- Entertainment and novelty -- The irresistibility of beauty -- Sociability -- An addictive vulnerability -- Our need for idols -- Self-esteem -- The social scene -- Alienation and isolation -- What makes us feel good? -- Mass media -- The perfect storm -- Entertainment addiction -- Entertainment as life fulfillment -- Transformation and obsession -- They got what I want -- Voyeurism exploited -- Epilogue -- References -- Index -- About the author.
Includes bibliographical references and index.
Keywords: Celebrities; Fans (Persons) -- Psychology; Fame -- Psychological aspects